Hematological, inflammatory, and hypoxia-responsive adaptations to 18-day normobaric live high-train low training in elite rowers - Kasperska, A.; Dziewiecka, H.; Jankowski, W.; Mikulski, T.; Czerniec, I.; Skarpanska-Stejnborn, A.; Ostapiuk-Karolczuk, J. (Frontiers in Physiology, 2026)
Introduction: The Live High-Train Low (LH-TL) altitude training method may stimulate erythropoietin (EPO) and vascular endothelial growth factor (VEGF) production, contributing to hematological and physiological adaptations. This study aimed to investigate the effects of an 18-day LH-TL protocol on hematological, inflammatory, and hypoxia-responsive biomarkers in elite rowers.